Silver Nanowire Transparent Conductive Film Prepared by Spin Coating: Correlating Network Morphology with Optical and Electrical Properties - Ni'matul Azizah; Buky Wahyu Pratama; Wardah Nabilah; Yeti Rafitasari (Mataram University, 2026)
In this study, silver nanowires (AgNWs) were synthesized through the polyol process and subsequently deposited onto glass substrates by a spin-coating technique to fabricate transparent conductive films. The morphology, optical properties, and electrical performance of the resulting films were investigated using scanning electron microscopy (SEM), UV–Vis spectrophotometry, and sheet resistance measurements. SEM observations confirmed the successful formation of AgNWs with an average diameter of 332 nm and a length of 28 µm. After film deposition, the AgNWs formed a dense and interconnected network with average dimensions of 178 nm in diameter and 12 µm in length. Optical characterization revealed a transmittance of 86.6% at 550 nm, indicating high transparency in the visible region. Electrical measurements showed a low sheet resistance of 3.3 Ω/sq, indicating good electrical conductivity of the fabricated film. The observed combination of high transmittance and low sheet resistance is attributed to the interconnected AgNW network morphology, in which numerous nanowire junctions provide effective electron transport pathways while the open regions between neighboring nanowires allow efficient light transmission. This correlation between network morphology and the resulting optical and electrical properties suggests that the fabricated AgNW film possesses characteristics suitable for transparent conductive electrode applications.